PREVALENCE OF ENDODONTIC PERIAPICAL LESIONS IN LATERAL ROOT-FILLED TEETH: A RADIOGRAPHIC STUDY - Mihaela Sălceanu; Cristina Dascălu; Tudor Hamburda; Agop-Forna Doriana; Claudiu Topoliceanu; Georgiana-Andreea Frumuzache; Alice-Teodora; Anca Melian (Romanian Dental Association for Education, 2024)
Aim of study. The aim of the present study was to assess the prevalence of periapical lesions in root-filled lateral teeth as well as the distribution of periapical lesions according to various factors that can influence the therapeutic outcome. Materials and method. The study group included 163 patients (gender: 58 males, 105 females; mean age 48.13 ± 14.708 yrs.) with at least 2-yrs. follow-up of 412 endodontically treated teeth. Following the radiographic assessment of the root and its periapical area, the root canal treatments were classified as adequate and poor, while the apical lesions was diagnosed on radiographic examen. The quality of coronal marginal sealing (poor, adequate) was assessed by radiographic examen. The distribution of apical lesion was assessed on socio-demographical parameters (gender, age groups), location (maxillary, mandibular), follow-up, quality of root canal filling, status of coronal marginal sealing, occlusal contacts, recurrent caries. Results. Periapical lesions prevalence in root-filled lateral teeth was as follows: gender (males- 47,3%; females- 50,2%); age groups (20-39 yrs.- 41,9%; 40-59 yrs.- 52,4%; ≥60 yrs.- 47,4%); follow-up (2-4 yrs.- 57,7%; 5-8 yrs.- 44,5%) (p=.010*); location (maxillary teeth- 46,1%; mandibular teeth- 54,5%). 58% of teeth with poor coronal marginal sealing, and 59% of teeth with poor root canal fillings were diagnosed with AP. Conclusions. Apical lesions were detected in 49.3% of the lateral root-filled teeth. Molars, poor root canals fillings, poor coronal marginal sealing, presence of recurrent caries were significantly associated with endodontic periapical lesions.